Rutaka footbridge in Rwanda: a low technology deck launch. Issue 3 (30th January 2019) - Towler, Ian; Mills, Brandon; Lofts, Matthew; Mills, Benjamin; Crosthwaite, Peter; Mistry, Divesh
Abstract : US charity Bridges to Prosperity has delivered over 250 simply designed and built footbridges around the world to provide rural communities with year-round safe access to markets, farms, schools, health clinics and other critical services. This paper describes the innovative design and construction of a 40 m suspended footbridge in Rutaka, Rwanda, which was completed in 2017. To reduce time working at height, the volunteer engineering team developed and trialled a low-technology method for launching the deck from a temporary platform, significantly improving safety and quality control. A photography-based community initiative also helped to convey the importance of maintaining the structure.